Kearifan Lokal Pemanfaatan Tumbuhan Berkhasiat Obat Masyarakat Desa Tahawa - Yanarita Yanarita; Yusintha Tanduh; Yosefin Ari Silvianingsih (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
The local wisdom in utilizing medicinal plants by the community of Tahawa Village in the tourist area of 'Sahai Tambi Balu' in Pulang Pisau Regency needs to be preserved as a form of conservation and to enhance the community's economy. The research was conducted using observation and in-depth interviews as the methods. The data analysis was done descriptively and qualitatively. The research findings in the tourist area of 'Sahai Tambi Balu' identified a total of 19 types of medicinal plants used by the community for treating various ailments. To collect medicinal plants from their natural habitat, certain protocols and permissions are required. Firstly, the community seeks permission from the Almighty God, and secondly, they seek permission from the medicinal plants themselves, as they are believed to possess a spirit or soul. Medicinal plants can provide benefits through their roots, stems, and leaves, each with its own method of usage. The manner of usage varies depending on whether it is for external or internal treatment, depending on the specific illness. Preserving the local wisdom of the community in harvesting medicinal plants is crucial for conservation efforts to protect the existence of these medicinal plants